The Effect of Internal Auditor's Competence and the Effectiveness of Internal Control on the Quality of Financial Statements with Professional Skepticism as a Moderating Variable - Agus Slamet Haryanto; Nurul Hidayah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to analyze the effect of the influence of internal auditor competence and the effectiveness of internal control on the quality of financial statements with professional skepticism as a moderating variable. The population in this study were 35 respondents at the Inspectorate of the Ministry of Youth and Sports. The sampling technique in this study is a saturated sample technique. The sample in this study was 35 respondents based on the Functional Position of Auditor and/or Supervision for the Implementation of Government Affairs (JFT) at the Inspectorate Office of the Ministry of Youth and Sports. The results in this study indicate that the competence of internal auditors and the effectiveness of internal control have a positive and significant effect on the quality of financial reports. This study proves that professional skepticism moderates the effect of internal auditor competence and the effectiveness of internal control on the quality of financial reports. Therefore, for further researchers to be able to conduct an ethnographic study.